Virtual textbooks as a means of implementing information-active approach in the classroom - Царенко, Олег (Educational Dimension, 2015)
Tsarenko O. N. Virtual textbooks as a means of implementing information-active approach in the classroom. In the article the methodical study of the overall approach to the organization of independent work of students in higher education institutions is given. The author formulates the problem of insolvency of information training, considers the structure of the virtual textbook on general physics, states the necessity of formulating Exercises that promote the professional development of staff.